2005
DOI: 10.1093/jaoac/88.5.1334
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Assurance GDS™ for E. coli O157:H7 Method and Assurance GDS for Shigatoxin Genes Method in Selected Foods: Collaborative Study

Abstract: A multilaboratory collaborative study was conducted to compare the Assurance GDS™ for E. coli O157:H7 method and the reference culture methods for the detection of E. coli O157:H7 in orange juice, raw ground beef, and fresh lettuce. A separate companion assay, the Assurance GDS for Shigatoxin Genes method was also evaluated with the same test portions. Fifteen laboratories participated in the study. A Chi square analysis of each of the 3 food types at the high, low, and uninoculated control levels was performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…The sample size of 65 g each was chosen for ease of use and because this is a common size used in the commercial setting for finished ground beef testing. Both experiments detected 100% of the spiked samples as positive for E. coli O157:H7 (Table 2) with GDS Ò or BAX Ò -RT systems, which is similar as other studies that reported detection rates near 100% by these two systems but using a smaller sample size (25 g per sample) and inoculations of 1e5 and 10e50 CFU per sample (Feldsine et al, 2005;Lionberg et al, 2003). Enumeration by PetriFilm AC plates showed exponential bacterial growth from each inoculation after the 8-h enrichment period.…”
Section: Detection Limits Of Nonviable E Coli O157:h7 Cells By Gds òsupporting
confidence: 86%
See 1 more Smart Citation
“…The sample size of 65 g each was chosen for ease of use and because this is a common size used in the commercial setting for finished ground beef testing. Both experiments detected 100% of the spiked samples as positive for E. coli O157:H7 (Table 2) with GDS Ò or BAX Ò -RT systems, which is similar as other studies that reported detection rates near 100% by these two systems but using a smaller sample size (25 g per sample) and inoculations of 1e5 and 10e50 CFU per sample (Feldsine et al, 2005;Lionberg et al, 2003). Enumeration by PetriFilm AC plates showed exponential bacterial growth from each inoculation after the 8-h enrichment period.…”
Section: Detection Limits Of Nonviable E Coli O157:h7 Cells By Gds òsupporting
confidence: 86%
“…Since meat products are highly perishable, rapid, accurate, and reliable methods that can detect the presence of E. coli O157:H7 at low levels are critical for meat safety control in the industry. To date, testing methods in a variety of formats for E. coli O157:H7 analysis in food products have been developed and evaluated (Ahmed et al, 2009;Arthur et al, 2005;Feldsine et al, 2005;Fratamico and Bagi, 2007). Among these, the real-time quantitative PCR (RT qPCR) has become one of the most commonly used methods for pathogen nucleic acid detection and quantification.…”
Section: Introductionmentioning
confidence: 99%